Effects of Porphyromonas gingivalis and Escherichia coli lipopolysaccharides on mononuclear phagocytes. - Roberts, F A (1997)
The mononuclear phagocyte plays an important role in the regulation of microbe-induced inflammation, in part through its ability to secrete mediators, particularly cytokines, in response to microorganisms and their products. To evaluate the effects of the microbial flora associated with chronic adult periodontitis on cytokine induction, lipopolysaccharide (LPS) from the periodontopathogen Porphyromonas gingivalis was used to stimulate naive and phorbol ester-primed U937 monocytic cells, as well as elutriated human peripheral blood monocytes. We assessed the effect of this LPS, in comparison to that of LPS from Escherichia coli, on cell proliferation, cytokine induction, and surface expression of the LPS receptor CD14. P. gingivalis LPS stimulated proliferation of U937 cells at concentrations of greater than 1 ng/ml, while E. coli LPS inhibited proliferation. Phorbol myristic acid (PMA)-treated U937 cells and elutriated monocytes responded to E. coli LPS activation by producing tumor necrosis factor alpha (TNF-alpha) mRNA and protein; however, P. gingivalis LPS induced greater numbers of TNF-alpha mRNA-positive cells and higher (P < 0.05) levels of protein than did E. coli LPS. Both cell types expressed interleukin-1 beta (IL-1beta) mRNA and protein in response to either LPS treatment. Compared with E. coli LPS, P. gingivalis LPS induced significantly (P < 0.05) higher numbers of IL-1 mRNA-positive U937 cells and elutriated monocytes, as well as production of significantly more (P < 0.05) IL-1 protein by the monocytes. The PMA-treated U937 cells and the monocytes produced high levels of IL-1 receptor antagonist mRNA and protein which were only marginally affected by the LPS preparations. While E. coli LPS induced expression of CD 14 on the surface of PMA-primed U937 cells and monocytes, P. gingivalis LPS exhibited a significantly (P < 0.05) greater ability to enhance receptor levels. Our results indicate that P. gingivalis LPS can activate the mononuclear phagocyte for proliferation, cytokine production, and CD14 expression, providing evidence for the potential of this bacterial component to act as a critical regulatory factor in the chronic inflammatory response associated with periodontitis.